Epidemiological characteristics and risk factors of multidrug-resistant tuberculosis in Luoyang, China - Wang, Zhenzhen; Hou, Yi; Guo, Tengfei; Jiang, Tao; Xu, Liang; Hu, Hongxia; Zhao, Zhanqin; Xue, Yun (Frontiers in Public Health, 2023)
Abstract Objective: We aimed to reveal the prevalence of multidrug resistant tuberculosis (MDR-TB) and the risk factors related in this region, guide clinical medication, and standardize anti-tuberculous treatment regimens. Methods: We retrospectively reviewed the high-resolution melting curve (HRM) results of 17,773 cases (of which 2,748 were positive) from June 2019 to May 2022 and analysed the prevalence of MDR-TB as well as the risk factors associated with it. Results: Of the 17,773 HRM results from June 2019 to May 2022, 2748 were HRM-positive and 312 were MDR-TB. The HRM positive and MDR-TB detection rates were 17.0% and 12.1% for males, as well as 12.4% and 8.2% for females, respectively. MDR-TB detection rate was higher in urban group (14.6%) than in rural (10.6%), and more frequently in group younger than 51 years (14.1%) than in group older than 50 years (9.3%). Notably, the MDR-TB detection rate of new patients in males was 18.3% higher than 10.6% in females, and the difference was statistically significant (p<0.001), while the MDR detection rate of females who had received anti-tuberculosis treatment (21.3%) was higher than that of males (16.9%). In the multivariate model, considering the results of sputum smear and detection time, MDR-TB was evidently positively correlated with history of tuberculosis (TB) treatment, younger than 51 years, urban, and male. Conclusion: Local TB infections are complex and diverse, and more comprehensive monitoring methods are needed to block the spread of MDR-TB.